Developing a contractual framework for outsourcing of facilities management - Maizan Baba, 1959-; Abdul Hakim Mohammed, 1959-; International Real Estate Research Symposium (2006 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2006)
22